The role of external and country specific factors in Hungarian inflation developments - Balázs Krusper (Magyar Nemzeti Bank, 2012)
Recent literature suggests that the co-movement of inflation is rather strong across countries. We use a factor model to asses this co-movement within the EU, while we differentiate between common (EU) and regional (CEE) effects. We find that price dynamics in Western European countries share a common pattern, while CEE countries can be divided into subgroups according to their inflation history. Results indicate that the monetary policy regime is a very important source of the difference among CEE countries. This method also allows us to examine how external and country-specific components contributed to the Hungarian inflation. We find that Hungary, similar to other countries in the region, experienced a disinflation period before the EU accession. However, country specific components (e.g. VAT changes or monetary policy) also played an important role.
Keywords: C33; E31; E42; E58; 330; inflation dynamics; factor model